Analisis Peran Pembiayaan Kredit Usaha Rakyat terhadap Pemberdayaan UMKM pada Masa Pandemi COVID-19 di Jawa Timur - Salsha Regita Adistia; Dimas Nugroho Dwi Seputro (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia’s economic resilience, yet their sustainability was severely challenged during the COVID-19 pandemic due to declining sales, liquidity constraints, and increased business risks. In response to these conditions, the government implemented the People’s Business Credit (KUR) program as a financing scheme to support MSMEs. This study aims to examine the factors influencing MSMEs’ access to KUR support during the pandemic in East Java. A quantitative approach was employed using logistic regression analysis, as the dependent variable KUR support was measured as a binary outcome. The study involved 219 MSMEs that had applied for or received KUR financing. The independent variables included installment obligations, payment difficulties, sales conditions, business profitability, business status, and business sector. The results indicate that payment difficulties, business profitability, and business status significantly influence access to KUR support, with business status emerging as the most dominant factor. Meanwhile, installment obligations, sales conditions, and business sector show no significant effect. The logistic regression model achieved an overall classification accuracy of 61.5 percent, indicating a moderate predictive capability. These findings suggest that KUR support during economic crises is primarily determined by business sustainability, legal-operational status, and financial performance of MSMEs.